2023
DOI: 10.3390/fire6020063
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Fuel Loads, Fire Hazard, and Carbon Emissions from Fires in Central Siberia

Abstract: The vast Angara region, with an area of 13.8 million ha, is located in the southern taiga of central Siberia, Russia. This is one of the most disturbed regions by both fire and logging in northern Asia. We have developed surface and ground fuel-load maps by integrating satellite and ground-based data with respect to the forest-growing conditions and the disturbance of the territory by anthropogenic and natural factors (fires and logging). We found that from 2001 to 2020, fuel loads increased by 8% in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Several studies have investigated the dynamics of forest fire behaviour and burnt areas in the different regions of the Russian Federation [13,[52][53][54][55][56]. These studies have revealed differences in the sensitivity of forest fire regimes to climate change and fire return interval (FRI) variability across the territory of the Russian Federation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the dynamics of forest fire behaviour and burnt areas in the different regions of the Russian Federation [13,[52][53][54][55][56]. These studies have revealed differences in the sensitivity of forest fire regimes to climate change and fire return interval (FRI) variability across the territory of the Russian Federation.…”
Section: Introductionmentioning
confidence: 99%
“…Wildfires are global phenomena that elicit widespread concern worldwide. They not only directly threaten the assets and values of human societies in fire-prone regions [1][2][3], but also have detrimental effects on critical ecosystem services [4], including air pollution [5,6] soil erosion [7], and carbon loss [8][9][10][11]. Furthermore, these threats are exacerbated by the increasing probability and severity of wildfires caused by global warming [12][13][14][15], amplifying the significance of wildfires as a concern.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al [7] indicated the following essential attributes for understanding fire behavior: fuel type, fuel biomass, fuel moisture, and fuel condition (live or dead). The fuel load is a crucial variable commonly used in various fire management strategies, such as fire risk assessments and fire behavior prediction [3,8]. The fuel load has a significant influence on the modeling of biomass and carbon estimates, and its knowledge for land managers is fundamental [9].…”
Section: Introductionmentioning
confidence: 99%